Tying resistance of reverse channel connection to concrete filled square and rectangular tubular sections. (1st October 2015) - Jafarian, M.; Wang, Y.C.
Highlights: Tying resistance for evaluation of structural robustness. Ultimate condition in CFT wall under tension in reverse channel connection flanges. Analytical method for calculating yield line resistance. Analytical method for calculating membrane action resistance. Analytical method for calculating maximum CFT deformation. Abstract: This paper presents the derivations of an analytical method to evaluate the tying resistance of reverse channel connection to rectangular/square concrete filled tube (CFT). The analytical derivations are based on results of an extensive series of numerical parametric study of this type of connection, covering a range of design parameters, including tubular section size, tubular section width to thickness ratio, reverse channel flange size and gap between the reverse channel flanges. Under a tying force, the tubular section may fail in two modes: formation of yield line mechanism or fracture under tensile membrane action in the tubular wall. In most cases, the membrane resistance governs. However, if the tubular section is thick, the yield line resistance is higher than the membrane resistance and membrane action does not develop. The tying resistance of the connection is the higher of the two values. This paper derives analytical equations for calculating these two typing resistance values. The membrane resistance depends on the ultimate lateral deformation of the tubular wall and this paper also presents a method for its calculation. Comparisons between the analytical calculation results and the numerical simulation results indicate that the proposed analytical equations give reasonably accurate calculations and the analytical method may be used in practical design.